2015
DOI: 10.1016/j.fertnstert.2015.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Results of centralized Asherman surgery, 2003–2013

Abstract: In 95% of women with Asherman syndrome, a healthy uterine cavity was restored with hysteroscopic adhesiolysis, in 1-3 attempts, with a 28.7% recurrence rate of spontaneous IUAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
89
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(94 citation statements)
references
References 22 publications
3
89
2
Order By: Relevance
“…The high recurrence rate of adhesions following hysteroscopic adhesiolysis in IUA remains one of the most difficult challenges in reproductive surgery . It is reported that increasing severity of disease is associated with lower pregnancy rate and a higher chance of requiring repeat surgery. Several studies have reported various methods to prevent adhesion reformation.…”
Section: Introductionmentioning
confidence: 99%
“…The high recurrence rate of adhesions following hysteroscopic adhesiolysis in IUA remains one of the most difficult challenges in reproductive surgery . It is reported that increasing severity of disease is associated with lower pregnancy rate and a higher chance of requiring repeat surgery. Several studies have reported various methods to prevent adhesion reformation.…”
Section: Introductionmentioning
confidence: 99%
“…IUAs can also result in infertility and miscarriage, and increase the risks of intrauterine growth restriction and disorders of placental implantation in subsequent pregnancies . The treatment of IUAs poses a challenge, and the prognosis of severe disease remains poor . Thus the prevention of IUAs is of great importance, and should focus on the management of any retained products of conception …”
Section: Introductionmentioning
confidence: 99%
“…This technique is costly, exposes the patient to ionizing radiation, and is technically challenging. Its advantages include use of a narrow hysteroscope, reduced risk of uterine perforation, and reduced risk of visceral damage should perforation occur, because no energy source is applied [65, 68]. A similar technique is described in an ambulatory setting using local anesthesia [69], with described success in mild adhesions only.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort of 683 women with moderate to severe adhesions treated surgically with postoperative adjuvants including one or a combination of IUD, balloon, estrogen, and hyaluronic acid reported a pregnancy rate of 314/475 (66%) with 201/314 (61%) resulting in a live birth [102]. A national referral center in the Netherlands reported menstrual outcomes for 638 consecutively treated women over a 10-year period [68]. The success rate, defined as normal menstruation, was 95%.…”
Section: Introductionmentioning
confidence: 99%